Development of a Novel Equilibrium Passive Sampling Device for Methylmercury in Sediment and Soil Porewaters. (9th January 2020) - Sanders, James P.; McBurney, Alyssa; Gilmour, Cynthia C.; Schwartz, Grace E.; Washburn, Spencer; Kane Driscoll, Susan B.; Brown, Steven S.; Ghosh, Upal
Abstract : Abstract: We explored the concept of equilibrium passive sampling for methylmercury (MeHg) using the strategy developed for hydrophobic organic chemicals. Passive sampling should allow prediction of the concentration of the chemically labile fraction of MeHg in sediment porewaters based on equilibrium partitioning into the sampler, without modeling diffusion rates through the sampler material. Our goals were to identify sampler materials with the potential to mimic MeHg partitioning into animals and sediments and provide reversible sorption in a time frame appropriate for in situ samplers. Candidate materials tested included a range of polymers embedded with suitable sorbents for MeHg. The most promising were activated carbon (AC) embedded in agarose, thiol–self‐assembled monolayers on mesoporous supports embedded in agarose, and cysteine‐functionalized polyethylene terephthalate, which yielded log sampler–water partition coefficients of 2.8 to 5 for MeHgOH and MeHg complexed with dissolved organic matter (Suwannee River humic acid). Sampler equilibration time in sediments was approximately 1 to 2 wk. Investigation of the MeHg accumulation mechanism by AC embedded in agarose suggested that sampling was kinetically influenced by MeHg interactions with AC particles and not limited by diffusion through the gel for this material. Also, AC exhibited relatively rapid desorption of Hg and MeHg, indicating that this sorbent is capable of reversible, equilibrium measurements. In sediment:water microcosms, porewater concentrations made with isotherm‐calibrated passive samplers agreed within a factor of 2 (unamended sediment) or 4 (AC‐amended sediment) with directly measured concentrations. The present study demonstrates a potential new approach to passive sampling of MeHg. Environ Toxicol Chem 2020;39:323–334. © 2019 SETAC